Product Specific Technical Assistance for Exports--Has It Been Effective? - Brenton, Paul; von Uexkull, Erik (2012)
The international community is placing increasing emphasis on aid for trade to assist low income countries to integrate into the global economy and to address their domestic constraints to export driven growth. There is, however, scant information on the effectiveness of previous support for export development to inform the design of new initiatives. In this paper, we exploit information on product specific technical assistance for trade and estimate a simple partial equilibrium model to assess the impact on the key measurable outcome--exports of the product subject to assistance. We apply a difference in differences approach to isolate the impact of the policy interventions and draw four main conclusions: on average, export development (ED) programs have coincided with or predated stronger export performance; such programs appear to be more effective where there is already significant export activity; there is some concern about the additionality of the programs and that support may be being channeled to sectors that would have prospered anyway; ultimately, conclusions strongly depend on what one postulates would have happened in the absence of the policy intervention, so the definition of a credible counterfactual is of utmost importance for the evaluation of technical assistance for exports.